Expression of receptor activator of nuclear factor κβ ligand (RANKL) and tumour necrosis factor related, apoptosis inducing ligand (TRAIL) in breast cancer, and their relations with osteoprotegerin, oestrogen receptor, and clinicopathological variables. Issue 7 (17th February 2006) - Cross, S S; Harrison, R F; Balasubramanian, S P; Lippitt, J M; Evans, C A; Reed, M W R; Holen, I
Abstract : Background: Receptor activator of nuclear factor κβ ligand (RANKL) has an important role in bone remodelling, and tumour necrosis factor related, apoptosis inducing ligand (TRAIL) can induce apoptosis in cancer cells. Their functions are linked by their interactions with osteoprotegerin (OPG). Objective: To investigate the expression of RANKL and TRAIL in a large series of unselected breast cancers and to analyse the relations between these expressions and the expression of OPG, oestrogen receptor, and clinicopathological variables. Methods: 395 breast cancers were sampled into tissue microarrays and immunohistochemistry undertaken for RANKL and TRAIL. Results: There was strong expression of RANKL in 14% of the cancers and strong expression of TRAIL in 30%. Expression of RANKL had a negative association with expression of oestrogen receptor (p = 0.036). Expression of TRAIL had a negative association with the Nottingham Prognostic Index (p = 0.021). There was a significant negative relation between expression of RANKL and TRAIL (p<0.005). Unsupervised cluster analysis produced a dendrogram that showed a clear division into two groups, and the expression of oestrogen receptor was significantly higher in one of those groups (p = 0.012). Conclusions: There is apparent loss of expression of RANKL in 86% of breast cancers; those tumours that retain expression tend to be oestrogen receptor negative and of a high histological grade. There is strong expression of TRAIL in 30% of breast cancers and these tend to be of better prognostic type. These results may be important in the processes of metastasis to bone and the apoptotic cell death pathway in cancer.